Dental care for early childhood in Brazil: from the public policy to evidence - Gustavo Essvein; Alexandre Baumgarten; Rafaela Soares Rech; Juliana Balbinot Hilgert; Matheus Neves (Universidade de São Paulo, 2019)
ABSTRACT OBJECTIVE: To evaluate whether characteristics of health services, oral health team and dental surgeon are associated with provision of dental care for children up to five years old in Brazilian Primary Health Care. METHODS: A cross-sectional study was conducted with data from 18,114 oral health teams in Brazil, evaluated in 2014 by the National Program for Access and Quality Improvement in Primary Care. The study outcome was the proven performance of dental procedures on children up to five years old. Statistical analysis was performed by Poisson regression based on a hierarchical model, where the first level was composed of service organization variables, the intermediate level composed of unit planning characteristics, and the proximal level composed of variables related to dental surgeon characteristics. RESULTS: Prevalence of dental care performed by oral health teams was 80.9% (n = 14,239). Scheduled appointments and activities of education in health were positively associated with the outcome, as well as planning and programming activities for the population and monitoring and analysis of oral health indicators. Complementary training in public health, continuing education activities and career plan were variables related to dental surgeons associated with the service provision. CONCLUSIONS: One fifth of health units in Brazil do not provide dental care for children in early childhood. Health units' well-structured organization and planning protocols are associated with the provision of this service, as well as better employment relationship and graduate activities for dental surgeons.